Urgensi Perencanaan Partisipatif dalam Pemberdayaan Ekonomi Masyarakat Desa (Studi Kasus Pemberdayaan Kelompok Perempuan Desa Pendabah) - Kurniyati Indahsari (Trunojoyo University of Madura, 2020)
Community empowerment programs often fail due to low community participation, weak facilitation processes, or lack of targeting. The research aims to determine the existing condition and describe how the participatory planning is able to formulate an agreed Strategic Action Plan of the Pendabah Village women's economic empowerment. Participatory planning process was implemented through a series of focus group discussions (FGDs) and in-depth interviews with Pendabah Village women's groups and other related parties. Research shows that the Family Welfare Empowerment group in Pendabah village has no activities and various community empowerment activities are not running well. Most parties are pessimistic about the successfulness of community empowerment programs in this village. However, community empowerment counselors remain optimistic since Pendabah community is open minded. The FGDs with women's groups, the socialization of woman empowerment success stories, and giving motivation to the group were conducted. As a result, a large empowerment project or program has been determined based on mutual agreement, identified current conditions related to the project, and formulated a Strategic Action Plan for Pendabah Village women's economic empowerment through the Home Yard Utilization Program.